Physical characteristics of traditional Malay settlement : A case study of Kg Morten and Kg Parit Sidang Seman,Melaka - Fatin Farhana N Murtaza (Kulliyyah of Architecture and Environmental Design,International Islamic University Malaysia, 2021)
The physical characteristics of the traditional Malay settlement is usually linked to the village’s environment, where the integration of social and cultural activities can be seen in the daily lives of the communities. However, the modernization of the settlement and rapid urban development around it have slowly diminished the characteristics and changed the physical characteristics of some settlements. Therefore, the objectives of this thesis are, i) to identify the physical characteristics of traditional Malay settlement through the selected case studies in Melaka, ii) to analyses the significance of the components of physical characteristics of traditional Malay settlement that are implemented in the case studies, iii) to propose the conceptual of the traditional Malay settlement based on the physical characteristics analysed in the case studies. This thesis examines the existing layout of two selected case studies in Melaka, namely Kg Morten and Kg Parit Sidang Seman, using an inventory, interview, and questionnaire approach, as well as the use of drone technology. This study considers five physical characteristics of traditional Malay settlements: house compound; house arrangement, distribution, and orientation; density; street network; and proximity. Based on the five components mentioned above, the key findings of this thesis are that both case studies show that the village environment is still preserved as the society and local authorities are concerned about the identity of the traditional Malay settlement. The significance of preserving the physical characteristics of traditional Malay settlements is identified as it improves the permeability and legibility of the settlement while also creating local identity through architectural design, historical and traditional culture of the settlement. In response to the objectives of this study, a conceptual for traditional Malay settlement based on physical characteristics has been created, which can be used as a reference to assist the authority and NGOs in the development of future settlements and the preservation of existing Malay settlements. Furthermore, theoretical studies may provide ideas and knowledge to specific agencies to assist them in planning and preserving the city's Malay identity. As a result of the exploration of the physical characteristics of traditional Malay settlement, this study has made an important contribution to the body of knowledge.